Solid Lipid Nanoparticles As Drug Carriers For Atovaquone - Mohtar, Noratiqah (2013)
Solid lipid nanoparticles of atovaquone (ATQ-SLNs) were prepared by high shear homogenization method using tripalmitin, trilaurin, and Compritol 888 ATO as the lipid matrix and hydrogenated soy lecithin, Tween 80 and, poloxamer 188 as the surfactants. Optimization of the formulations was conducted using 6 sets of 24 factorial design study based on four independent variables which were homogenizing cycle, concentration of lipid, concentration of main surfactant, and concentration of co-surfactant. The dependent variables were particle size and polydistribution index. The effect of the four independent variables towards the responses was analyzed using ANOVA and response surface plots. Finally, the best formulations with the highest entrapment efficiency were chosen from each lipid system which were TPT 8 and TLT 16 for tripalmitin and trilaurin system, respectively, while Compritol 888 ATO was excluded for further study. Lyophilization process by using trehalose as the cryoprotectant was done to improve stability of both formulations. Incorporation of trehalose during homogenization process showed an improvement in the particle size and entrapment efficiency when compared to the incorporation after homogenization in both formulations. TLT 16 DH was selected as the final formulation with an average diameter of 84.63 ± 1.51nm before and 217.9 ± 8.42nm after lyophilization, and entrapment efficiency of 93.57 ± 3.07% before and 66.04 ± 1.74% after lyophilization process.